Achiral bis-imine in combination with CoCl2: A remarkable effect on enantioselectivity of lipase-mediated acetylation of racemic secondary alcohol - Arunkumar, K.; Reddy, M. Appi; Kumar, T. Sravan; Kumar, B. Vijaya; Chandrasekhar, K. B.; Kumar, P. Rajender; Pal, Manojit (Beilstein Journal of Organic Chemistry, 2010)
A bis-imine (prepared via a new FeCl3-based method) in combination with CoCl2 facilitated lipase-mediated acetylation of the (R)-isomer of a racemic benzylic secondary alcohol with 91% ees. The methodology was used for the preparation of the known drug rivastigmine.
Keywords: acetylation; bis-imine; cobalt chloride; enantioselectivity; lipase